Meckel's diverticulum with intussusception in a 5-year-old patient with Down's syndrome. (24th December 2014) - Anwar, Mohammed Omer; Ahmed, Hamza Ibn; Al Hindi, Saeed; Al Omran, Yasser
Abstract : Meckel's diverticulum is understood to be the commonest congenital malformation within the gastrointestinal tract with a prevalence of 2%, as found on autopsy studies. Although many cases are asymptomatic, complications can occur including haemorrhage, diverticulitis, chronic ulceration and intestinal obstruction. Intussusception is also a complication, but extremely rare. We present a rare case of Meckel's diverticulum causing intussusception, which was surgically resolved, in a 5-year-old girl. Our aim through this case report is to generate greater awareness of this complication and to provide some potential guidance towards its treatment.